PELAYANAN TRANSPORTASI PARIWISATA PT. TUNAS ANTARNUSA MUDA DI KOTA PEKANBARU - Ivan Ronevel Gomgom Julius Sihombing; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The tourism sector relies heavily on the quality of consumer experience, where land transportation, particularly tourism buses, serves as the backbone of tourist mobility. PT. Tunas Antarnusa Muda (TAM) is one of the bus transportation service providers in Pekanbaru City, catering to various travel needs with a diverse fleet. This study aims to identify tourist responses to the tourism transportation services of PT. Tunas Antarnusa Muda in Pekanbaru City and to examine the relationship between tourist profiles and the quality of services provided. The method used in this research is descriptive quantitative. Data were collected by distributing questionnaires to approximately 250 respondents selected using the accidental sampling technique. The data analysis technique includes descriptive statistics to measure the mean value. The results indicate that, overall, the tourism transportation services at PT. Tunas Antarnusa Muda (TAM) are in the "High" category. This is reflected in the scores obtained for each dimension of service quality (TERRA). In the Tangible dimension, supporting facilities such as toilets, pillows, and blankets received the highest appreciation with a score of 4.09. In the Empathy dimension, a score of 4.11 was achieved for the crew's patience in handling complaints. In the Reliability dimension, the highest score of 4.11 was recorded for the statement regarding buses departing according to the predetermined schedule. In the Responsiveness dimension, the highest score of 4.13 was achieved for the crew's promptness in responding to customer complaints. Finally, in the Assurance dimension, the highest average score was obtained by the indicator of the crew's extensive knowledge regarding routes and destinations, with a score of 4.16. Keywords: Transportation Services, Tourism Bus, PT. Tunas Antarnusa Muda, Pekanbaru.